2013
DOI: 10.5888/pcd10.120224
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Analysis of Fast-Food Chain Restaurant Menus Before and After Implementation of Local Calorie-Labeling Policies, 2005–2011

Abstract: IntroductionSince 2008, several states and municipalities have implemented regulations requiring provision of nutrition information at chain restaurants to address obesity. Although early research into the effect of such labels on consumer decisions has shown mixed results, little information exists on the restaurant industry’s response to labeling. The objective of this exploratory study was to evaluate the effect of menu labeling on fast-food menu offerings over 7 years, from 2005 through 2011.MethodsMenus f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 18 publications
1
51
0
3
Order By: Relevance
“…Restaurants may be responsive to modifying menus in response to consumer demand for more information. Some studies have found that healthy menu options increased after menu-labeling enactment (12, 64), although none noted a difference in the overall menu caloric content (11, 16, 72). Beyond labeling, implementation of nutritional standards for restaurants has also been proposed (28).…”
Section: Government Policiesmentioning
confidence: 99%
“…Restaurants may be responsive to modifying menus in response to consumer demand for more information. Some studies have found that healthy menu options increased after menu-labeling enactment (12, 64), although none noted a difference in the overall menu caloric content (11, 16, 72). Beyond labeling, implementation of nutritional standards for restaurants has also been proposed (28).…”
Section: Government Policiesmentioning
confidence: 99%
“…Studies at larger scales may benefit from remoteassessment methods, for instance using Internet menus, circulars, or other business advertisements (particularly for chain stores and restaurants that have consistent offerings across sites). [84][85][86] If actual assessments are not possible, studies should again include sensitivity analyses (eg, *Select list of 35 published studies available from the author upon request.…”
Section: Recommendationmentioning
confidence: 99%
“…9 But in a study that provides evidence suggestive of a telltale heart effect, Namba et al (2013) combed an archive of publicly accessible web pages for changes in posted menu offerings at fast food restaurants between 2005 and 2011, a period during which several municipalities introduced calorie posting. Menus from 5 fast-food chains with outlets in areas subject to menu-labeling laws were compared with menus from 4 chains operating in areas not requiring labeling.…”
Section: The Spotlight and The 'Telltale Heart' Effectmentioning
confidence: 99%